2007
DOI: 10.1507/endocrj.k06-127
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Atorvastatin on Bone Turnover in Male Patients with Hypercholesterolemia

Abstract: Abstract. No consensus has been reached on whether the 3-hydroxy 3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, known as statins, have beneficial effects on bone health. The purpose of our study was to evaluate the effects of atorvastatin on bone metabolism by means of measuring bone turnover markers in male patients with hypercholesterolemia both at diagnosis and prospectively after 3 months of treatment. Twenty-two Japanese male patients (mean age 62.36 ± 10.1 years) with untreated hypercholeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…In a recent study of ours, we reported that atorvastatin improved accelerated bone turnover in dyslipidemic male patients, especially in those with lower HDL-C [28]. All these observations would suggest that bone turnover markers, preferably along with BMD, should be monitored in dyslipidemic patients, especially male patients with lower HDL-C, to effectively prevent bone loss and subsequent fracture.…”
Section: Discussionmentioning
confidence: 65%
“…In a recent study of ours, we reported that atorvastatin improved accelerated bone turnover in dyslipidemic male patients, especially in those with lower HDL-C [28]. All these observations would suggest that bone turnover markers, preferably along with BMD, should be monitored in dyslipidemic patients, especially male patients with lower HDL-C, to effectively prevent bone loss and subsequent fracture.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the use of drugs for the treatment of metabolic disorders, such as type 2 diabetes and atherosclerosis, has shown to impact bone metabolism (Herrington & Potvin Klein 2001, Majima et al 2007. In this regard, we recently reported that both GLP-1 and Ex-4 have osteogenic effects in two insulin resistance and type 2 diabetic rat models (Nuche-Berenguer et al 2009, 2010a.…”
Section: Discussionmentioning
confidence: 99%
“…It now seems to be clear that this apparent protection is a consequence of the mechanical loading imposed by high body weight in this condition (Rosen & Bouxsein 2006, Pereira et al 2007. In fact, hypercholesterolemia appears to contribute to the pathogenesis of osteoporosis in postmenopausal women, which might justify the use of cholesterol-lowering statins as putative therapies in this situation (Herrington & Potvin Klein 2001, Tanko et al 2003, Majima et al 2007). In the Zucker diabetic fatty rat model, osteopenia was prevented by the administration of insulin-sensitizing agents lowering hyperlipidemia and hyperglycemia (Shibata et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…TCa measurements were corrected for albumin conand aminobisphosphonates which exert strong effects on both bone and lipid metabolism [7,14]. as a matter of fact, the two last agents share the same metabolic mevalonate pathway, recently proposed as essential for not only the synthesis of cholesterol but also the regulation of bone cell proliferation and osteoclast apoptosis [15].…”
Section: Laboratory Measurementsmentioning
confidence: 99%